Satellite-based estimation of biomass carbon stocks for northeast China's forests between 1982 and 1999 - Tan, Kun; Piao, Shilong; Peng, Changhui; Fang, Jingyun (Forest Ecology and Management, 2007)

Meta-analysis and its application in global change research - Lei, XiangDong; Peng, ChangHui; Tian, DaLun; Sun, JianFeng (Chinese Science Bulletin, 2007)

Dominant factors controlling glacial and interglacial variations in the treeline elevation in tropical Africa - Wu, Haibin; Guiot, Joël; Brewer, Simon; Guo, Zhengtang; Peng, Changhui (Proceedings of the National Academy of Sciences, 2007)
The knowledge of tropical palaeoclimates is crucial for understanding global climate change, because it is a test bench for general circulation models that are ultimately used to predict future global warming. A longstanding issue concerning the last glacial maximum in the tropics is the discrepancy between the decrease in sea-surface temperatures reconstructed from marine proxies and the high-elevation decrease in land temperatures estimated from indicators of treeline elevation. In this study, an improved inverse vegetation modeling approach is used to quantitatively reconstruct palaeoclimate and to estimate the effects of different factors (temperature, precipitation, and atmospheric CO 2 concentration) on changes in treeline elevation based on a set of pollen data covering an altitudinal range from 100 to 3,140 m above sea level in Africa. We show that lowering of the African treeline during the last glacial maximum was primarily triggered by regional drying, especially at upper elevations, and was amplified by decreases in atmospheric CO 2 concentration and perhaps temperature. This contrasts with scenarios for the Holocene and future climates, in which the increase in treeline elevation will be dominated by temperature. Our results suggest that previous temperature changes inferred from tropical treeline shifts may have been overestimated for low-CO 2 glacial periods, because the limiting factors that control changes in treeline elevation differ between glacial and interglacial periods.

A Simulation of Temporal and Spatial Variations in Carbon at Landscape Level: A Case Study for Lake Abitibi Model Forest in Ontario, Canada - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Chen, Jiaxin; Parton, Sue (Mitigation and Adaptation Strategies for Global Change, 2007)

Growth and structure development of semi-natural larch-spruce-fir (Larix olgensis–Picea jezoensis–Abies nephrolepis) forests in northeast China: 12-year results after thinning - Lei, Xiangdong; Lu, Yuanchang; Peng, Changhui; Zhang, Xiaopeng; Chang, Jie; Hong, Lingxia (Forest Ecology and Management, 2007)

Building a "Green" Railway in China - Peng, Changhui; Ouyang, Hua; Gao, Qiong; Jiang, Yuan; Zhang, Feng; Li, Jun; Yu, Qiang (Science, 2007)

Carbon storage by ecological service forests in Zhejiang Province, subtropical China - Zhang, Jun; Ge, Ying; Chang, Jie; Jiang, Bo; Jiang, Hong; Peng, Changhui; Zhu, Jinru; Yuan, Weigao; Qi, Lianzhong; Yu, Shuquan (Forest Ecology and Management, 2007)